Counter-Narrative of Shi'ism in The Hadith Text of Kitab “Al-Faraid Al-Saniyah” KH. Sya'roni Ahmadi Kudus - Arif Friyadi (International Journal Ihya' 'Ulum al-Din, 2023)
The beginning of the emergence of Shi'ism initiated by a Jew, Abdullah bin Saba' had made considerable conflict among the companions at that time. The friction tapered when the killing of Ali bin Abi Talib and his son Husain in Karbala'. From year to year, the emergence of Shi'ism in several Middle Eastern countries led to the country's disintegration. The conflict of Imamiyah that leads to bloodshed seems to have no end at all times. Of course, this should not happen in Indonesia, which is known as a plural country. Of this problem, some scholars are called to write a book to counter Shi'aism in Indonesia. One is KH Sya'roni Ahmadi, with the text 'al-Faraid al-Saniyah.' This paper aims to explore KH. Sya'roni Ahmadi's thoughts on preventing the development of the Shi'a sect in Indonesia. This paper is categorized as qualitative research by comparing literature and interviews with the family of the book's author directly. The results showed that KH Sya'roni's role in increasing the existence of Aswaja in Indonesia needs to be appreciated. This is a form of his vocation to protect the country from disintegration and sect divisions.